Penguin and Proteus. Imagination as Otherness in me - Sabolius, Kristupas (Religija ir kultūra, 2007)
The question of Otherness is usually taken into account while discussing the Ego’s relation with Others as well as with the World. This article is based on the premises that the function of phantasy melts the subjectivity, revealing the perspective of intersubjectivity within it. On this purpose Sartre’s, Husserl’s and Merleau-Ponty’s researches on the function of imagination, which elucidate the image as the boundary slipping from the centre of Ego, are compared to the story of Hollywood’ movie „Fight Club“. The penguin, which appears in one of the episodes, registers the moment of egological schism, thus becoming the revelation and incarnation of phantasy. While the playful, autonomous and multiform character of imaginary is cleared out, we can ascertain, speaking in Kantian terms, that it has not a complementary or intermediary function, but, in the genesis of transcendental subject, plays the paradoxical role of „allien innerness“ or „inner alienity“. Thought remaining always beside, imagination is a catalyzer which enables crystallization of transcendental forms.